Amphiphilic fluorescent copolymers via one-pot combination of chemoenzymatic transesterification and RAFT polymerization: synthesis, self-assembly and cell imaging. Issue 4 (8th December 2014) - Huang, Zengfang; Zhang, Xiqi; Zhang, Xiaoyong; Fu, Changkui; Wang, Ke; Yuan, Jinying; Tao, Lei; Wei, Yen
Abstract : A novel one-pot strategy for the fabrication of AIE-based FONs has been developed via a combination of RAFT polymerization and enzymatic transesterification. Abstract : The development of fluorescent organic nanoparticles (FONs) based on aggregation induced emission (AIE) dyes has attracted significant research interest in recent years. In this work, a novel one-pot strategy for the fabrication of AIE-based FONs was developed via a combination of RAFT polymerization and enzymatic transesterification for the first time. During this procedure, a hydrophobic tetraphenylethene-functionalized AIE dye (denoted as TPEOH) with a hydroxyl end functional group and a hydrophilic polyethylene glycol monomethyl ether (mPEG-OH, M n = 350) were simultaneously attached onto the methacrylate monomer via enzymatic transesterification. The amphiphilic copolymer formed after RAFT polymerization of the functionalized methacrylate monomers tended to self-assemble into FONs with the hydrophobic AIE core covered by a hydrophilic PEG shell. The molar fractions of TPE and PEG in the polymer were about 30.5% and 69.5%, respectively, while M n was 4700 g mol −1 with a narrow polydispersity index (PDI) (∼1.30). The obtained amphiphilic polymer nanoparticles (denoted as TPE-PEG) demonstrated good fluorescence performance and excellent dispersibility in aqueous solution. More importantly, these FONs possessed a spherical morphology with a uniform size (about 200 nm) and excellent biocompatibility, making them promising for bioimaging applications.